Native lactic acid bacteria as a starter culture for the production of Mexican cream cheese - Cobo-Monterroza, Rodrigo (2019)
Introduction. The bacterial starter cultures are successfully used in the production of artisan cheeses, since they help to maintain sui generis sensory characteristics, as well as controlling the presence of pathogens. It has been reported that natives strains are the best options to perform this function. Objective. The aim of this research was to evaluate the effect of the addition of lactic acid bacteria (LAB) isolated from the traditional process of cheese making, as a starters in the manufacture of cream cheese from pasteurized milk. Materials and methods. The research was done in the Ocosingo city, Chiapas, Mexico, during the months of February to November from 2016. 37 strains with different morphology were isolated, from milk, cheese and whey, of which 21 were Gram positive, catalase and peroxidase negative. For their acidifying capacity, eight strains were selected, with which six treatments were formulated (combinations of three strains). Results. The treatment that was most accepted by consumers was restructured into three new treatments (three combinations of two strains). Of these new treatments, that one (T8) where two LABs (2S and 30Q) were combined was similar in color, firmness and fat content to the control (cream cheese made with unpasteurized milk). Although they were slightly different in protein, moisture and ash content, however, expert panelists found no significant differences (proof of discrimination A not A) between the T8 cream cheese and the control. This same treatment promoted microbiological counts (aerobic mesophilic, total coliforms, and molds and yeasts) lower than those established by the sanitary standards. Conclusion. The use of BAL 2S and 30Q as starter culture allowed a cream cheese to be obtained from pasteurized milk with similar characteristics to traditional cream cheese, besides microbiologically safe.